Laplacian-based Design: Sketching 3D Shapes - Sheng, Bin; Wu, Enhua (International Journal of Virtual Reality, 2006)
The sketch-based shape modeling is one of the most challenging and active problems in computer graphics. In this paper, we present an interactive modeling system for generating free-form surfaces using a 2D sketch interface. Since inferring 3D shape from 2D sketches is an one to many function with no unique solution, we propose to interpret the given 2D curve to be the projection of the 3D curve that has minimum curvature among all the candidates in 3D. In this way, firstly, we present an algorithm to efficiently find a close approximation of this minimum curvature 3D space curve. In the second step, our system could identify the 3D surfaces automatically, and then we apply Delaunay triangulation on these surfaces. Finally, the shape of the triangular surface mesh that follows the 3D profile curves is computed using harmonic interpolation by solving Laplacian equations. We present experimental results on various kinds of drawings by the interactive modeler